Answer:
r = 2
s = 4
t = 3
Explanation:
Given:
r = 2(s - t)
or
r = 2s - 2t .............(1)
2t = 3( s - r) ...............(2)
r + t = 2s - 3 .............(3)
substituting 1 in 3, we get
2(s - t) + t = 2s - 3
or
2s - 2t + t = 2s - 3
or
-t = 2s - 3 - 2s
or
t = 3
substituting t in 3 we get
r + 3 = 2s - 3
or
r = 2s - 6
substituting r and t in 2, we get
2 × 3 = 3( s - (2s - 6))
or
2 = s - 2s - 6
or
- 4 = -s
or
s = 4
substituting value of s and t in 1 , we get
r = 2 ( 4 - 3 )
or
r = 2
thus,
r = 2
s = 4
t = 3